Explaining China's Development and Reforms - Hofman, Bert; Wu, Jinglian (World Bank, Washington, DC, 2017)
China's remarkable economic performance over the last 30 years resulted from reforms that met the specific conditions of China at any point in time. Starting with a heavily distorted and extremely poor economy, China gradually reformed by improving incentives in agriculture, phasing out the planned economy and allowing non-state enterprise entry, opening up to the outside world, reforming state enterprises and the financial sector, and ultimately by starting to establish the modern tools of macroeconomic management. The way China went about its reforms was marked by gradualism, experimentation, and decentralization, which allowed the most appropriate institutions to emerge that delivered high growth that by and large benefited all. Strong incentives for local governments to deliver growth, competition among jurisdictions, and strong control of corruption limited rent seeking in the semi reformed system, whereas investment in human capital and the organizations that were to design reforms continued to provide impetus for the reform process. Learning from other countries' experience was important, but more important was China's adaptation of that experience to its own particular circumstances and needs.